A rare case report of conjoined twins: Thoraco-omphalopagus with anterior abdominal wall defect - Trivedi, Swati; Khokher, Santosh; Trivedi, Shashank; Rastogi, Prasoon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Conjoined twins are a rare deviation of monozygotic monoamniotic twins which results from fusion of the two at any part of their body. The prognosis is not good and associated with high mortality. Here we report a case of conjoined twin which was referred to our tertiary care hospital as twin pregnancy with impacted breech in obstructed labour. Taking mothers condition into account, she was taken for emergency caesarean section, performing which we realised that it was a conjoined twin. The baby were still born and conjoined at thorax and abdomen (thoraco-omphalopagus) with anterior abdominal wall defect in one and unrevealed sex in other. Current report emphasizes on making an early diagnosis of conjoined twin pregnancy, so that it can be managed at the earliest according to the gestational age.